The commenters’ reading positions in an online news article’s comment column: A speech act analysis on media discourse - Asidiky, Zakie; Puspa, Vindy Melliany (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
This study investigated the commenters’ reading positions in an online news article’s comment column. The first theory that coined the reading position is Stuart Hall. Based on Hall's theory, there are three reading positions for the readers in interpreting a text. First is the dominant or hegemonic reading position that means the readers who fully share the text, receive, and then reproduce it. Second is the negotiated reading position; it means the readers who do not fully share the text yet generally receive it. In this position, they sometimes refuse and modify the text by reflecting their positions, experiences, interests, or even contradictions. The third is the oppositional or counter-hegemonic reading position; it means the readers whose social situation places them in direct opposition relationships with the text. They understand the text but do not share it and reject it. In this study, the researcher used the speech act theory to describe and find out the commenters’ reading positions in the selected data. There are 42 comments have written on the comment column of an online news article entitled ‘Singles in Indonesia are in trouble and under pressure: study’ that was shared on Facebook. The researcher used the qualitative descriptive method for analyzing the data. The results are 14 commenters were identified in the hegemonic reading position, 17 commenters in the negotiated reading position, and 11 commenters in the oppositional reading position.